2020
DOI: 10.3390/ijerph17186536
|View full text |Cite
|
Sign up to set email alerts
|

Workload, Workaholism, and Job Performance: Uncovering Their Complex Relationship

Abstract: The current study aimed to test how workload, via workaholism, impacts job performance along with the complex interplay of perfectionistic concerns and work engagement in this mediated relationship. A two-wave, first and second stage dual-moderated mediation model was tested in an SEM framework. Results based on a sample of 208 workers revealed a complex and nuanced relationship among the studied constructs, such that the simple mediation model was not significant, but the indirect effect was negative, nonsign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 90 publications
(126 reference statements)
5
46
0
3
Order By: Relevance
“…There are also some important distinctions to make regarding the outcomes. Different from workaholism, work engagement is known as a healthy and productive form of heavy work investment, which is associated with many positive outcomes and may moderate the relationship between workaholism and negative outcomes (Scafuri Kovalchuk et al, 2019;Spagnoli et al, 2020). From this perspective, organizations should strive to promote work engagement in a way that limits the possibility of workaholism.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…There are also some important distinctions to make regarding the outcomes. Different from workaholism, work engagement is known as a healthy and productive form of heavy work investment, which is associated with many positive outcomes and may moderate the relationship between workaholism and negative outcomes (Scafuri Kovalchuk et al, 2019;Spagnoli et al, 2020). From this perspective, organizations should strive to promote work engagement in a way that limits the possibility of workaholism.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…To explore this role, we chose to focus on workload because it is a prominent stressor in the modern workplace (see Reid & Ramarajan, 2016) and a powerful predictor of job-related affective well-being and stress outcomes such as burnout (e.g., Ilies, Dimotakis, & Pater, 2010). Higher levels of workload may be particularly problematic for work addicted since work addiction has been found to be related with obsessive compulsive disorder and adult attention deficit hyperactivity disorder (Andreassen, Griffiths, Sinha, Hetland, & Pallesen, 2016), which include symptoms such as poor organization, obsessiveness and rigid perfectionism (see also Atroszko et al, 2020;Clark, Lelchook, & Taylor, 2010;Spagnoli et al, 2020). Such symptoms do not help in dealing effectively with high workload and actually may lead to the accentuation of the strain reactions associated with workload.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Although workaholism has been also associated with positive attributes such as very high work effort [ 7 ], job satisfaction, and eustress [ 8 , 9 ], findings have consistently supported a negative view of workaholism, documenting its relationships with decreased mental health [ 10 ], and higher levels of negative emotions and anxiety [ 11 , 12 ], burnout [ 13 ], elevated blood pressure [ 14 ], and sickness absence [ 15 ]. Additionally, the notion that workaholics may perform better than their colleagues has been questioned, since the former have perfectionistic tendencies, including rigidity, inflexibility, and difficulties in delegating tasks [ 16 , 17 ], which are not instrumental to job performance. Indeed, a recent study found that workaholism was not associated with a supervisor-related measure of job performance [ 11 ], suggesting that there may be little advantage of being a workaholic for both individuals and organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace bullying has been mainly investigated from the perspective of the victim [ 16 ] and by frequently focusing on poor work environmental conditions as antecedents, such as workload, role conflict and ambiguity, and organizational change [ 28 , 29 , 30 , 31 ]. However, a number of studies have taken the perspective of the perpetrator (see [ 23 , 24 ]), suggesting that personal characteristics, such as neuroticism, hostile personality, and low emotional stability/self-regulatory capacity, may play a role as antecedents of the enactment of bullying.…”
Section: Introductionmentioning
confidence: 99%